2004
DOI: 10.1016/j.msea.2004.04.066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-glide stresses on the plastic flow of single and polycrystals of molybdenum

Abstract: The Schmid law, which has been ubiquitously utilized in large-scale continuum computations, asserts that only the shear stress acting in the slip plane in the slip direction controls the plastic deformation. This rule is accurate for fcc metals but it does not apply in bcc metals owing to the spacial spreading of the core of screw dislocations that control their plastic deformation. In this paper we present resulsts of atomic-level simulations of the effect of externally applied stresses on 1/2[1 1 1] screw di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…In order to take these effects into account, the approach of Bassani et al [266] and Vitek et al [267] is adopted, where the effect of non-glide stress is incorporated in the model by modifying the critical resolved shear stress according to:…”
Section: Driving Forces and Kinetic Relations For Transformation And mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to take these effects into account, the approach of Bassani et al [266] and Vitek et al [267] is adopted, where the effect of non-glide stress is incorporated in the model by modifying the critical resolved shear stress according to:…”
Section: Driving Forces and Kinetic Relations For Transformation And mentioning
confidence: 99%
“…The deformation rates in such cases are typically orders of magnitude above realistic scales so that the transfer of such information must be done with great care since the results cannot in all cases be used for low-rate deformation constitutive models that typically prevail in CPFE simulations. Therefore, it may be more pertinent for molecular dynamics simulations of plasticity to provide certain constants or mechanisms for improved formulations of dislocation core structures, mobility, non-Schmid behavior, dislocation reactions, damage initiation and hardening mechanisms [265][266][267]. Other combinations are conceivable where a continuum-scale FE method is used for a proper boundary condition treatment around a simulation regime that is treated by an atomistic method.…”
Section: Challenges and Open Questionsmentioning
confidence: 99%
“…Due to the lack of close-packed planes in BCC crystals, there is no clear consensus among researchers on which planes crystallographic slip occurs, though, experimentally, slip appears to occur mainly on the f1 1 0g f and f1 1 2g f planes. Simulations have suggested that glide on the f1 1 2g f planes is in fact composed of alternating short slip steps on the f110g f planes (see Vitek et al, 2004), although this is still a somewhat open issue. As mentioned in Section 2.2, the amount of plastic slip in high-carbon martensite is very limited and is not accounted for in the model.…”
Section: Slip Systems Transformation Systems and Materials Parametersmentioning
confidence: 99%
“…[64][65][66][67] Furthermore, studies of the motion of screw dislocations in molybdenum revealed the significance of stresses perpendicular to the slip direction on the onset of plastic deformation. 68,69 In iridium, unlike in any other fcc metal, two core structures for the screw dislocation have been found. A transformation between these two structures may lead to an exceptionally high rate of cross slip during plastic deformation and associated rapid increase in the dislocation density and strong local hardening.…”
Section: Introductionmentioning
confidence: 99%